2021
DOI: 10.1088/1361-648x/ac2ca7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of helium flux on near-surface helium accumulation in plasma-exposed tungsten

Abstract: We report results of object kinetic Monte Carlo (OKMC) simulations to understand the effect of helium flux on the near-surface helium accumulation in plasma-facing tungsten, which is initially pristine, defect-free, and has a (100) surface orientation. These OKMC simulations are performed at 933 K for fluxes ranging from 1022 to 4 × 1025 He/m2 s with 100 eV helium atoms impinging on a (100) surface up to a maximum fluence of 4 × 1019 He/m2. In the near-surface region, helium clusters interact elastically with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The importance of the vacancy-trapping mechanism increases as temperature increases. Nandipati et al [89] investigated the effect of helium flux on helium bubble behavior in more detail. They found that nearly no helium was retained near the surface for low fluxes (10 22 m −2 s −1 ) without pre-existing traps, which is in good agreement with the results by Yang et al [58].…”
Section: Long-term Evolution Of Helium Accumulation and Surface Morph...mentioning
confidence: 99%
“…The importance of the vacancy-trapping mechanism increases as temperature increases. Nandipati et al [89] investigated the effect of helium flux on helium bubble behavior in more detail. They found that nearly no helium was retained near the surface for low fluxes (10 22 m −2 s −1 ) without pre-existing traps, which is in good agreement with the results by Yang et al [58].…”
Section: Long-term Evolution Of Helium Accumulation and Surface Morph...mentioning
confidence: 99%